Pathogenicity of two species of entomopathogenic agents to subterranean termite Coptotermes gestroi Wasmann (Isoptera: Rhinotermitidae) in laboratory. Pathogenic effcts of two species of entomopathogenic agents, Metarhizium anisopliae and Bacillus thuringiensis A ard B, were trested to subterranean termite Coptotermes gestroi Wasmann in laboratory. Three groups of rhc tcrti ite tclor.ker:s were each e.xposed to a treated filter paper with one of the entomopathogenic agents for one minute. Twenty - Paimin Sukartana; Rusti Rushelia; Widi Rumini (Buletin Hama dan Penyakit Tumbuhan, 2000)
Pathogenicity of two species of entomopathogenic agents to subterranean termite Coptotermes gestroi Wasmann (Isoptera: Rhinotermitidae) in laboratory. Pathogenic effcts of two species of entomopathogenic agents, Metarhizium anisopliae and Bacillus thuringiensis A ard B, were trested to subterranean termite Coptotermes gestroi Wasmann in laboratory. Three groups of rhc tcrti ite tclor.ker:s were each e.xposed to a treated filter paper with one of the entomopathogenic agents for one minute. Twenty-five termite workers and three soldiers were then transferred to a wetfilter paper disk that had been installed in a plastic vial. The test materials were stored in a dark and humid at room temperature for 14 dc j'.s. Five replicates were provided. Observations were conducted daily to determine termite nlortality urld take out dead termites. Reszllts showed that the fungus M. anisopliae was more pathogenic than Bt. A and B. After being exposed to treated paper with the fungus, all test termites died within 8-10 days. Treatments with B. thuringierisis A and B did not produce high mortality, and seemed to be not different from the control, only causing less than 3% termite mortality until the end of the tests.